c-Met inhibition in aHOXA9/Meis1model of CN-AML - Mulgrew, Nuala M.; Kettyle, Laura M.J.; Ramsey, Joanne M.; Cull, Susan; Smyth, Laura J.; Mervyn, Danielle M.; Bijl, Janet J.; Thompson, Alexander (Wiley, 2013)
Background: Hematopoiesis is a paradigm for developmental processes, hierarchically organized, with stem cells at its origin. Hematopoietic stem cells (HSCs) replenish progenitor and precursor cells of multiple lineages, which normally differentiate into short-lived mature circulating cells. Hematopoiesis has provided insight into the molecular basis of tissue homeostasis and malignancy. Malignant hematopoiesis, in particular acute myeloid leukemia (AML), results from impaired development or differentiation of HSCs and progenitors. Co-overexpression of HOX and TALE genes, particularly the HOXA cluster and MEIS1, is associated with AML. Clinically relevant models of AML are required to advance drug development for an aging patient cohort. Results: Molecular analysis identified altered gene, microRNA, and protein expression in HOXA9/Meis1 leukemic bone marrow compared to normal controls. A candidate drug screen identified the c-Met inhibitor SU11274 for further analysis. Altered cell cycle status, apoptosis, differentiation, and impaired colony formation were shown for SU11274 in AML cell lines and primary leukemic bone marrow. Conclusions: The clonal HOXA9/Meis1 AML model is amenable to drug screening analysis. The data presented indicate that human AML cells respond in a similar manner to the HOXA9/Meis1 cells, indicating pre-clinical relevance of the mouse model.